An evaporation induced self-assembly approach to prepare polymorphic carbon dot fluorescent nanoprobes for protein labelling. Issue 93 (6th November 2018) - Li, Lei; Lian, Zhongyu; Yan, Xi; Xia, Meng; Zhang, Mingcui
Abstract : Herein, we report a novel route to prepare polymorphic carbon dot fluorescent probes via the evaporation-induced self-assembly of glutaraldehyde and carbon dots, which first usually form carbon nanoclusters which then could self-assemble to form carbon nanocrystals, nanospheres or nanofibers in different ionic strength solutions at room temperature. Abstract : Herein, we report a novel route to prepare polymorphic carbon dot fluorescent probes via the evaporation-induced self-assembly of glutaraldehyde and carbon dots, which first usually form carbon nanoclusters which then could self-assemble to form carbon nanocrystals, nanospheres or nanofibers in different ionic strength solutions at room temperature. The aldehyde functionalized polymorphic C-dot fluorescent probe can easily covalently bond with amino groups on proteins.